Parasitological Examination of Fecal Samples from Sheep, Goats, and Cattle at the Techiman Slaughterhouse - Dwaah Prince Kyere; Nana Yaa Awua-Boateng; Anothny Osei-Tutu; Solomon Bakyaayele; Mohammed Abdul-Nafiw Leppode (Journal of Parasite Research, 2025)
This study investigates the parasitological examination of faecal samples collected from sheep, goats, and cattle at the Techiman Slaughterhouse. Initially, 341 samples were collected, which were subsequently sorted to 327 for analysis due to the loss of data for 14 samples. The primary aim was to identify the prevalence of parasitic infections and assess the health implications for livestock and public health. The samples were analyzed using qualitative and quantitative parasitological techniques, including flotation and sedimentation methods, to detect nematode and cestode eggs. Descriptive statistics were used to summarize the data and the prevalence of each parasite type. The findings reveal significant levels of parasitic infections, particularly strongyle ova and Moniezia expansa, highlighting the need for better management practices in livestock health.
Keywords: Parasitology